2012
DOI: 10.1007/s00198-012-1940-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of smoking on bone metabolism

Abstract: Osteoporosis is a common, morbid and costly disorder characterized by deterioration in bone strength. Cigarette smoking is associated with reduced bone mineral density (BMD) and increased fracture risk. There are basic, clinical, and observational studies that define several of the underlying pathophysiologic mechanisms that predispose smokers to bone loss. Such mechanisms include alterations in calciotropic hormone metabolism and intestinal calcium absorption, dysregulation in sex hormone production and metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
178
1
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(193 citation statements)
references
References 121 publications
4
178
1
10
Order By: Relevance
“…The effect of smoking is also influenced by dose and duration [42], which can explain diverging study results. Longitudinal studies of adolescent boys and girls in early adulthood have shown adverse effect of smoking [21,43].…”
Section: Discussionmentioning
confidence: 90%
“…The effect of smoking is also influenced by dose and duration [42], which can explain diverging study results. Longitudinal studies of adolescent boys and girls in early adulthood have shown adverse effect of smoking [21,43].…”
Section: Discussionmentioning
confidence: 90%
“…67 Lifestyle choices may also confer additional risk for BMD deficits. In adults, smoking, caffeine, and alcohol intake are all associated with reduced BMD, [68][69][70] and these behaviors should be avoided in children and adolescents.…”
Section: Exercise and Lifestylementioning
confidence: 99%
“…Numerous studies have linked smoking with low BMD, osteoporosis and osteoporotic fracture. Initial reports indicated that men and women who smoked had lower BMDs than nonsmokers of the same age and sex 2,[20][21][22] . Although the effects of cigarette smoking on BMD and osteoporosis have been described, a similar effect of smokeless tobacco use on osteoporosis has never been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism for this effect is unknown, there may be several possible explanations 6) . Nicotine induces vasoconstriction, low tissue oxygenation, tissue ischemia 6,24) and effects osteoblastic bone formation and osteoclastic bone resorption 22) . Additionally, non-nicotine constituents of tobacco have a direct effect on bone cells 25,26) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation